2013
DOI: 10.3892/ijo.2013.2220
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Galium verum aqueous extract on growth, motility and gene expression in drug-sensitive and -resistant laryngeal carcinoma cell lines

Abstract: Galium verum, also known as Lady's Bedstraw, is a herbaceous perennial plant of the family Rubiaceae, native to Europe and Asia and used in traditional medicine as an anticancer medicine. It is used as a decoction in most traditional recipes, applied externally as well as internally. We produced a Galium verum decoction and applied it in vitro to chemosensitive (Hep-2 and HLaC79) and chemoresistant, P-glycoprotein-overexpressing (Hep2-Tax, HLaC79-Tax) laryngeal carcinoma cell lines. It could be demonstrated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 39 publications
1
30
0
Order By: Relevance
“…On sensible primary mucosal cells, showing no p-glycoprotein expression, however, Galium decoction proved to be less toxic than in the HLaC78 laryngeal cancer cell line. In general, high motility of tumour cells is frequently correlated with increased chemoresistance, as previously shown for the paclitaxel-resistant head and neck cancer cell line Hep2-Tax (20). In HLaC78 cells, high cellular motility is combined with a slow division rate and chemosensitivity.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…On sensible primary mucosal cells, showing no p-glycoprotein expression, however, Galium decoction proved to be less toxic than in the HLaC78 laryngeal cancer cell line. In general, high motility of tumour cells is frequently correlated with increased chemoresistance, as previously shown for the paclitaxel-resistant head and neck cancer cell line Hep2-Tax (20). In HLaC78 cells, high cellular motility is combined with a slow division rate and chemosensitivity.…”
Section: Discussionmentioning
confidence: 64%
“…Potential main agents in Galium extracts, used for the present and previous study are chlorogenic acid, Luteolin-7-O-glucoside and rutoside (20). Chlorogenic acid has been shown to be antimetastatic in vivo and in vitro in a variety of tumour systems (30)(31)(32).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 ). HLaC79-Tax is a descendant cell line of HLaC79 with acquired resistance against paclitaxel and corresponding over-expression of p-glycoprotein [ 17 ]. Here, the EC 50 dose of O. regalis extract was higher in HLaC79-Tax (20.6 μg/ml) compared to the parental cell line HLaC79 (9.9 μg/ml).…”
Section: Resultsmentioning
confidence: 99%
“…Other studies showing THM compounds displaying antiresistance impacts were also reported. For example, Galium verum aqueous extract profoundly suppressed cell invasion in Taxol-resistant human laryngeal carcinoma [55]. Danshen extract significantly inhibited proliferation of etoposide-and Taxol-resistant human oral cancer cells [112].…”
Section: Thm Extracts Modulate Therapeutic Sensitivity In Hnsccsmentioning
confidence: 99%